Effects of selenium and vitamin E supplementation on concentrations of plasma thyroid hormones in lambs - Naziroglu, M; Cay, M; Tahan, V; Bal, R; Delibas, N (Scientific Technical Research Council Turkey, 1998)
An attempt was made to determine the effects of selenium and vitamin E supplementation on thyroid hormones in lambs. Sixteen Akkaraman lambs were used and divided equally into four groups. One group was used as a control. Second group was fed with selenium (sodium selenite, 0.3 mg kg(-1) feed). Third group was fed with vitamin E (DL-alpha tocopheryl acetate, 250 mg-1 feed) and fourth group was fed with selenium (sodium selenite, 0.3 mg/ kg(-1) feed) + vitamin E (DL-alpha tocopheryl acetate, 250 mg kg(-1) feed) supplemented diet. Serum selenium, vitamin E and plasma thyroxine (T-4) and tri-ioda-thronine (T-3) were measured at 1st, 5th, 10th weeks. levels of T3 were slightly increased and both levels of T4 and ratio of T4/T3 were slightly decreased when vitamin E, selenium and vitamin E plus selenium were supplemented to the diets of lambs. The levels of serum vitamin E were significantly higher (p<0.01) in vitamin E and vitamin E plus selenium supplemented groups than that in the control group. However, the levels of serum selenium were significantly higher (P<0.05, P<0.01) in both vitamin E and selenium supplemented lambs thant of that in control. Results in this study, there was no effects of selenium and vitamin E supplementation on plasma thyroid hormones in lambs. However, vitamin E had an increasing effect on serum selenium level, despite that selenium did not effect serum vitamin E levels.
Keywords: selenium; vitamin E; thyroxine (T4); tri-iodo-thyronine (T3); lamb